ANALISIS TITIK IMPAS USAHATANI TANAMAN KETEPENG CINA (Cassia alata L) PADA PT. SRIKAYA SEGA UTAMA BANJARBARU - Zulipah Mahdalena; Norhalimah Norhalimah (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
The study aims to determine the technical processing of candle bush total cost, total revenue, income and break even point. The method used in this research is survey method with observation technique participation. The sampling method by means of case studies. Results of this research note total cost at Rp. 631.602.236,7 total revenue Rp. 950.400.000,00 , Profit Rp. 318.797.763,3 and the Break even point in units of 63.600,76 kg, the Break even point in selling Rp. 101.761.218,00.